Abruzzo and Sicily: Catching up and lagging behind - Rodolfo Helg; Giovanni Peri; Gianfranco Viesti (EIB Papers, 2000)
Would you expect twins to reach different heights? The comparison is perhaps not so accurate, but in the early 1950s Abruzzo and Sicily were economically very similar. Both were 'full members' of the underdeveloped Mezzogiorno, with little industry, few natural resources, poor transport infrastructure, high agricultural employment and a low standard of living. Yet, while Abruzzo has managed a substantial catch-up, Sicily has remained a lagging region. Consider regional GDP per capita compared to that in the North of Italy as the single most powerful indicator of this. From the early 1950s to the mid-1990s, Abruzzo increased its relative position by almost 25 percentage points. Over the same period, Sicily managed to climb up by only 2 percentage points relative to the north. This paper assesses the determinants of the diverging paths between these regions. It is organised as follows. After having provided a broader overview of the development of the Mezzogiorno in the next section, Section 3 focuses in more detail on the performances of Abruzzo and Sicily. Growth accounting exercises will show that the role of total factor productivity growth - technological change - had a much more important role in Abruzzo than it did in Sicily. At the same time, Abruzzo had a much broader based development, including a range of manufacturing activities and market services. Development in Sicily was much more specialised, and relied heavily on investment in a few capital intensive industries. Section 4 discusses the implications of these different development strategies, and tries to identify the role of government policy in the process. Section 5 summarises and concludes.
Keywords: 330; Wirtschaftswachstum; Abruzzen; Sizilien